Trends in dermatology consultations in the COVID‐19 era in Cameroon - Edgar Mandeng Ma Linwa; Odette Berline Sigha; Angelique Jacquie Djeumen Touka; Charlotte Eposse Ekoube; Esther Eleonore Ngo Linwa; Michael Ngenge Budzi; Martin Geh Meh; Henry Fomukong Nzozone; Emmanuel Armand Kouotou; Anne‐Cecile Zoung Kanyi Bissek (Wiley, 2022)
Abstract Introduction With the advent of COVID‐19, a highly infectious viral pandemic, first declared in Cameroon in March 2020, access to expert dermatology care was postulated to decrease. We carried out a descriptive study to understand the epidemiology of skin diseases amongst patients consulting at an outpatient dermatology clinic and its variations with the onset of COVID‐19. Methods We conducted a retrospective database study over a period of 2 years at Laquintinie hospital, Cameroon. Two periods were distinguished: 1 March 2019 to 29 February 2020 (pre‐COVID‐19 era) and 1 March 2020 to 28 February 2021 (COVID‐19 era). Results Overall, 5946 patients with one or more clinical conditions were analysed. The most common age group described was young adults (18-40 years). Females consulted twice as much as males (M/F ratio; 1:1.7). The mean age was 28.9 (±18.0) years with an age range of 1 month to 89 years. Infectious dermatoses predominated. However, the single most prevalent dermatologic condition was acne. There was a 35.6% drop in consultation frequency in the COVID‐19 era. Conclusion Three in four patients consulting at dermatology clinic are below 40 years, with a female predominance. Epidemiological profile of dermatoses in Cameroon is similar to that in the rest of Africa. Consultation frequency decreased in the COVID‐19 era but trends in consultations were rather unaltered except for patients above 50 years where eczema and scabies increased. More studies should be conducted to understand these trends better at a national level and envisage training of health personnel on prevalent dermatoses.